Statins in Hepatitis B and C Patients is Associated with Reduced Hepatocellular Carcinoma Risk - Ume Rooman, Sehrish Shahani, Fiza Shaikh, Sadna, Raj Patel (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and represents a major global health burden. Chronic infection with the hepatitis B virus (HBV) and hepatitis C virus (HCV) is a well-established etiological factor for HCC, contributing to more than 75% of global cases. Given the increasing burden of HCC and the need for effective preventive strategies beyond antiviral therapy, a comprehensive synthesis of available evidence regarding the chemopreventive role of statins in HBV or HCV-infected individuals is warranted. This systematic review aims to evaluate and quantify the association between statin use and HCC risk among patients with hepatitis B or C. Objective: To determine whether statin therapy reduces the risk of HCC in this high-risk population. Materials and Methods: This systematic review was conducted in accordance with PRISMA guidelines and included studies retrieved from PubMed, Google Scholar, the Cochrane Library, and the Directory of Open Access Journals (DOAJ). Eligible studies involved patients with HBV or HCV, evaluated the use of statins as the intervention, and compared outcomes with non-statin users, specifically focusing on the risk of developing hepatocellular carcinoma. Only original research articles published in English between January 2019 and April 2025 were included. The quality of all included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool. Results: Among the 15 studies included in our review, 14 studies found that statins were associated with a lower risk of HCC in patients infected with Hepatitis B or C. Only one study did not report statistically significant results for viral hepatitis. In our pool of included studies, 3 studies found a dose-dependent protective effect against HCC. Although statins are primarily lipid-lowering drugs, some studies report a greater effect of lipophilic statins in reducing HCC risk. Conclusion: We found an overall positive association between the use of statins and a reduced risk of HCC in HBV and HCV patients, with evidence supporting a dose-dependent relationship. Lipophilic statins were found to be more efficacious. However, further research is needed to establish the optimal doses and statin types, as well as their use in patients with multiple comorbidities, before physicians can empirically prescribe statins to HBV and HCV patients. Keywords: Hepatitis B, Hepatitis C, Hydroxymethylglutaryl-CoA Reductase Inhibitors, Hepatocellular Carcinoma, Antineoplastic Agents